Professional Certification, Reward Systems, and Public Financial Performance: The Mediating Role of Work Motivation - Anita Erari (Greenation Research & Yayasan Global Resarch National, 2025)
The focus of this study is to answer whether the competency policy and reward system actually improve the performance of Expenditure Treasurers substantially, or whether its effectiveness depends entirely on the depth of work motivation formed within the apparatus. This study was conducted in the work unit (satker) managing the State Budget within the working area of the Jayapura State Treasury Service Office (KPPN). The study population consisted of 275 Expenditure Treasurers. Based on the criteria for determining a representative sample size, a sample of 164 Expenditure Treasurers was taken. The sampling technique used Simple Random Sampling. The results of data analysis and discussion, this study summarizes seven points including Certification has a positive and significant effect on Work Motivation, Rewards have a positive and significant effect on Work Motivation, Work Motivation has a positive and significant effect on Performance, Certification has a positive and significant effect on Performance, Rewards have no significant effect on Performance, Work Motivation significantly mediates the relationship between Certification and Performance, Work Motivation significantly mediates the relationship between Rewards and Performance.